VERIFIKASI QUR'ANI TENTANG STATUS ANAK ANGKAT - Nuraini Nuraini (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2017)
The phenomenon of adoption or adoption in society has become commonplace. This is in addition to the religiously justified, the state of Indonesia also protect it. The adoption of children is not forbidden in Islam and even includes noble deeds if based on sincerity and rules in accordance with the teachings of Islam, but in practice there are many treatments that are contrary to the teachings of Islam. Not a few of the people who treat adopted children exactly the same as their children so that in terms of mahram, guardianship and inheritance get the right as a natural child. From the results of verification of verses of the Qur'an about adopted children it is known that the adopted child if there is no relationship mahram then the status is the same as others. In other words, the law that applies to others then so does the adopted child. Therefore, matters relating to the mahram must be preserved, trust is not applicable and inheritance is not obtained except on the permissible limits on behalf of the gift.